Restorative Justice Reconstruction with The Indonesian Criminal System After Law No. 1 of 2023 - RIYADI, Padlah (Protection: Journal Of Land And Environmental Law, 2024)
The reform of criminal law in Indonesia through the new Criminal Code adopts the principle of Restorative Justice, with the formulation of restorative criminal acts, opening up opportunities to make it the basis for reforming criminal law in the future. Discussion, ratification, and implementation of the draft Criminal Code following the current Indonesian values are no longer by the nation's culture based on Customary Law and other diverse values. This research is normative, conceptualizing law as a written rule or norm that becomes a standard of behavior. The data used is secondary data, including primary, secondary, and tertiary legal materials related to Restorative Justice. Research results: The implications of Restorative Justice after ratifying the RKUHP into the Criminal Code Law reflect fair and dignified law. The substance of Restorative Justice is spread across various articles, including Article 51, which emphasizes the purpose of punishment to re-educate prisoners with forgiving divine values. This principle underlies the belief that humans can change towards goodness despite misbehaving. Article 52 of the Criminal Code Law emphasizes that punishment must not degrade human dignity. It can be concluded that the substance of restorative justice that has been facilitated in the Criminal Code Law, articles 51, 52, 53, 54 and especially Article 132, which states that the authority to prosecute is null and void if a settlement has occurred outside the judicial process, is relevant to the idea and purpose of the law itself.